1998
DOI: 10.1096/fasebj.12.13.1391
|View full text |Cite
|
Sign up to set email alerts
|

Theagoutigene product inhibits lipolysis in human adipocytes via a Ca2+‐dependent mechanism

Abstract: Overexpression of the murine agouti gene results in obesity. The human homologue of agouti is expressed primarily in human adipocytes, and we have shown recombinant agouti protein to increase adipocyte intracellular Ca2+([Ca2+]i) and thereby stimulate lipogenesis. However, since recent data demonstrate that increasing adipocyte [Ca2+]i may also inhibit lipolysis, we have investigated the role of agouti-induced [Ca2+]i increases in regulating lipolysis in human adipocytes. Short-term (1 h) exposure to recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
126
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(135 citation statements)
references
References 36 publications
7
126
0
1
Order By: Relevance
“…13,17 In addition, elevated [Ca 2 þ ]i also inhibits lipolysis, leading to an expansion of adipocyte triglyceride storage. 5,16 Conversely, the decrease in [Ca 2 þ ]i observed with increasing calcium appears attributable to suppression of circulating 1a, 25-dihydroxyvitamin D. 9,18,19 Consistent with this, data from our laboratory have demonstrated that 1a, 25-dihydroxyvitamin D induces rapid [Ca 2 þ ]i influx in adipocytes, whereas a specific membrane vitamin D receptor antagonist (1b, 25-dihydroxyvitamin D) blocked this effect. 4 This indicated a non-genomic action of 1a, 25-dihydroxy Role of 1a, 25-Dihydroxyvitamin D in adipocyte X Sun and MB Zemel vitamin D via a putative membrane vitamin receptor, which later was identified as the 1, 25D 3 -MARRS, 20 in modulating…”
Section: Role Of 1a 25-dihydroxyvitamin D In Adipocyte X Sun and Mb supporting
confidence: 55%
See 1 more Smart Citation
“…13,17 In addition, elevated [Ca 2 þ ]i also inhibits lipolysis, leading to an expansion of adipocyte triglyceride storage. 5,16 Conversely, the decrease in [Ca 2 þ ]i observed with increasing calcium appears attributable to suppression of circulating 1a, 25-dihydroxyvitamin D. 9,18,19 Consistent with this, data from our laboratory have demonstrated that 1a, 25-dihydroxyvitamin D induces rapid [Ca 2 þ ]i influx in adipocytes, whereas a specific membrane vitamin D receptor antagonist (1b, 25-dihydroxyvitamin D) blocked this effect. 4 This indicated a non-genomic action of 1a, 25-dihydroxy Role of 1a, 25-Dihydroxyvitamin D in adipocyte X Sun and MB Zemel vitamin D via a putative membrane vitamin receptor, which later was identified as the 1, 25D 3 -MARRS, 20 in modulating…”
Section: Role Of 1a 25-dihydroxyvitamin D In Adipocyte X Sun and Mb supporting
confidence: 55%
“…15,16 Increasing [Ca 2 þ ]i in adipocytes via either receptor-or voltage-mediated Ca 2 þ channel activation stimulated fatty acid synthase expression and activity. 13,17 In addition, elevated [Ca 2 þ ]i also inhibits lipolysis, leading to an expansion of adipocyte triglyceride storage.…”
Section: Role Of 1a 25-dihydroxyvitamin D In Adipocyte X Sun and Mb mentioning
confidence: 99%
“…STAT5A is shown for each group to demonstrate even loading of the samples. olism in cultured adipose cells in vitro (19,47). Although the agouti gene is not normally expressed in adipose tissue in the mouse, we were able to induce the expression of high levels of agouti in white and brown adipose tissue by expressing the cloned mouse gene under the control of the aP2 promoter.…”
Section: Discussionmentioning
confidence: 95%
“…8 We have reported that 1a, 25-(OH) 2 -D 3 plays a direct role in the modulation of adipocyte Ca 2 þ signaling, resulting in an increased lipogenesis and decreased lipolysis. 18,19 In addition, 1a, 25-(OH) 2 -D 3 also plays a role in regulating human adipocyte UCP2 expression, suggesting that the suppression of 1a, 25-(OH) 2 -D 3 and the resulting upregulation of UCP2 may contribute to increased rates of energy utilization. 10,11 Accordingly, the suppression of 1a, 25-(OH) 2 -D 3 by increasing dietary calcium attenuates adipocyte triglyceride accumulation and caused a net reduction in fat mass in both mice and humans in the absence of caloric restriction, 13 a marked augmentation of body weight and fat loss during energy restriction in both mice and humans, 13,20 and a reduction in the rate of weight and fat regain following energy restriction in mice.…”
Section: Discussionmentioning
confidence: 99%